EFFECT OF EDUCATIONAL INTERVENTION MEASURES ON KNOWLEDGE ABOUT RABIES AND ITS PREVENTIVE MEASURES AMONG FINAL YEAR NURSING STUDENTS OF A TERTIARY CARE HOSPITAL IN CENTRAL INDIA - Dixit, Sanjay; Raghunath, Deepa; Bhagwat, Anil; Taneja, Gunjan; Singh, Arvind; Sahu, Anurag; Gupta, Abhishek; Sahu, Ashsish (Indian Journal of Community Health, 2012)
Background: Rabies continues to be a major public health challenge with around 55,000 deaths every year. Amongst the health care providers nursing personnel are often the first point of contact and hence need to be well trained in the management of rabies cases. Methods: The present study was an educational intervention study conducted among 100 final year nursing students of a Medical College Hospital to assess the knowledge regarding rabies and its transmission, first aid measures undertaken, and pre and post exposure prophylaxis measures employed to prevent the infection. Results: 66% of the students knew about the signs and symptoms of the disease, post intervention this increased to 87%. Knowledge regarding animal bites which transmit rabies improved by 86 % mode of transmission by 49 % and first aid measures undertaken following an animal bite by 12%. 15% of the students knew about the correct site and route of PEP; post intervention 91% knew about it, 87% increase was observed as regards the dose of vaccine to be administered and 73% students correctly knew about the PEP schedule post educational intervention. Knowledge regarding groups / individuals who need to receive pre-exposure prophylaxis increased by 33% and that of the schedule of pre-exposure prophylaxis by 53%. The mean pre-intervention score was 6.95 and mean post-intervention score was 13.51; the results being statistically significant. Conclusion: Substantial improvement in knowledge about the disease was noted amongst the nursing students following the educational intervention session.